Modelagem e projetos de amplificadores Raman distribuidos - Procopio, Cesar Augusto de Souza (2007)
In the last years, the gradual increase of the information traffic has stimulated continuous development of echnologies, devices and systems that support this growth. Optical amplification systems have proved to be the most efficient way to support this traffic. These systems have progressively used Raman Amplifiers as loss compensators, in their non-regenerated very long-haul links. In this work, a numerical code was designed to analyze the signal propagation into non-regenerated systems with only Raman amplification. Their signals and pumps are transmitted through non-external modulation CW lasers, and they suffer the most important propagation effects on this system. Analysis of these effects and characteristics of optical systems and subsystems are very important for the modeling of Raman Amplifiers, for better fit these devices to topological and functional characteristics necessary to the systems. After comparing this code with commercial software and with experimental results, this code will determine quality parameters of any configurations and circuits present in a long-haul experimental optical network, during the transmission of sixteen DWDM channels with a 0.8nm separation between channels, and located in a 1.5THz flattened band centered in #31 channel (λ = 1552,52nm).